The understanding and meaning of knowledge transfer for research and education - Helga Kanning; Christiane Meyer (Spatial transformation: Processes, strategies, research design, 2022)
Knowledge transfer between universities and society, as well as the social commitment of universities ('third mission'), are coming increasingly into the focus of public attention and of science policy (section 2). The central role of universities in supporting search and learning processes in society, as well as the need for a change in mindset towards (more) sustainable development, are also emphasised in the context of the Great Transformation towards greater sustainability (section 3). At present, the two strands of discussion are largely unconnected. This article outlines the basic aspects of both fields of knowledge. This demonstrates that the basic understanding is the same in both areas: they share an understanding of knowledge transfer based on recursive exchange processes between science and society, which ideally entail the joint generation (co-production) of knowledge which can be linked both to science and to practice. However, there are 'blind spots' which will be illuminated by focusing on transformative education, an area still marginalised in the debate about transformation. Philosophical and educational reflections (section 4) demonstrate that deeper cultural and individual values, as well as holistic worldviews - i.e. based on the unity of humans, nature and culture - appear to be suitable key orientations for radical transformations towards sustainability. From the authors' perspective, the communication of normative target/orientation knowledge and its scrutiny in scientificallygrounded debates in line with a transdisciplinary understanding of science - in combination with a reflection on the values and mindsets embedded in a holistic education in relation to the environment or values - represents a central 'hinge' for knowledge transfer and for the path from knowledge to action. These aspects are currently underrepresented and deserve more attention in research and development.
urn:nbn:de:0156-08910228; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Third mission; transfer as recursive exchange; transformative research/education; shift in consciousness/shift of mindsets; transformative literacy; transformative learning; change agents; values education; worldviews